케이팝(K-pop)을 활용한 한국어 연어 교육 방안 연구 - 방탄소년단(BTS) 노래를 중심으로 - 박영희; Park¸ Young-hee; 오성아; Oh¸ Sung-ah; 노하나; Noh¸ Ha-na (인문학연구, 2021)
본 연구는 케이팝(K-pop)을 활용한 한국어 연어 교수법에 대한 것이다. 한국어 학습자들이 어휘 학습 시 어려움을 겪는 부분이 연어이다. 그래서 연어 학습의 어려움을 줄이고 효과적인 연어 학습을 위해 케이팝(K-pop)을 활용하여 실제적인 연어 수업 교육 방안을 모색하고자 하였다. 먼저 본고에서 연어의 개념을 ‘긴밀한 결합 관계가 있는 단어들의 관계’라고 정리하고 그 범위를 문법적 연어와 어휘적 연어로 분류하였다. 그리고 연구 대상의 범위를 어휘적 연어로 제한하여 방탄소년단(BTS) 노래에 나타난 어휘적 연어를 분석하였다. 노랫말 속에 나타난 연어 표현은 총 241개이며 유형별로 체언+용언형 135개(56%), 부사+용언형 29개(12.4%), 부사어+용언형 19개(7.5%), 체언(의) 체언형 11개(4.6%), 관형사형+체언 47개(19.5%)로 나타났다. 이것을 가지고 한국어 연어 사전과 학습자 말뭉치 용례와 대조하여 한국어 학습을 위한 2차 연어 목록 97개를 선별하였고 연어 학습에 도움이 될 수 있도록 실제적인 교수 방안도 제시해 보았다. 연어는 그 특성이 복잡하여 한국어 학습자들이 어려움을 겪는 부분이지만 자연스러운 언어 사용을 위해서는 반드시 필요한 학습이기도 하다. 한국어 학습자들이 친근하게 다가갈 수 있는 케이팝(K-pop)을 통해서 여러 가지 형태의 연어 학습이 이루어진다면 다양한 언어 상황에 맞는 자연스러운 한국어 표현이 가능할 것이다. This research is about the collocation teaching method of Korean using K-pop. It is collocation that Korean language learners have difficulty in learning Korean. We try to seek the realistic collocation teaching method using K-pop to reduce the difficulty in learning collocation learning and for effective collocation learning. The collocation is identified as ‘the relationship between words which have close combination relation. And the range of the collocation is classified into a grammatical collocation and a lexical collocation. The range of research is limited to the lexical collocation and the lexical collocations in BTS’ song are analyzed. There are total 241 collocations in the lyrics including 135(56%) noun- predicate, 29(12.4%) adverb+ predicate, 19(7.5%) adverb+predicate, 11(4.6%) nominal noun, and 47(19.5%) adnominal+noun type. 97 collocations were selected for the second collocation for Korean learning in comparison with the collocations dictionary and learner corpus usage. With this, we present the practical teaching method to help learn the collocations. Since the collocation has complex traits, the learners have difficulty in learning the collocation but it is surely necessary to learn the collocation for using Korean naturally. The spontaneous Korean expressions corresponding to various language use situations could be used if the learners can learn various types of collocations using K-pop, which is Korean language learners can approach easily. learners can approach easily.